WAYS OF USING UZBEK FOLKLORE-SUB-GENRES IN THE EDUCATION OF STUDENTS BY TEACHING THEM IN PRIMARY GRADES (American Journal of Pedagogical and Educational Research, 2023)
In this scientific article information about the ways of using Uzbek folklore-sub-genres in the education of students through the teaching of Uzbek folklore-sub-genres in primary classes are highlighted, and methodical recommendations on the importance of folklore are given in it.The purpose of writing this article: to show the importance of using Uzbek folklore-sub-genres in the education of students by teaching them in primary grades.Methods and Games: "Find the name of the fairy tale", "Salad from fairy tales", "Find the video".….Results: educating the young generation in the spirit of understanding the essence of Uzbek folklore.